The Effect of Training Emotion Regulation Techniques on Resilience and Psychological Well-Being among Nurses in Zahedan - Nikmanesh, Zahra; Khosravi, Zohre (Advances in Nursing & Midwifery, 2020)
Abstract Introduction: Nurses constitute the largest part of human resources in the health system and play critical roles in taking care of and improving patients' health. This study aimed to examine the effect of training emotion regulation techniques on resilience and psychological well-being among nurses. Methods: This is a quasi-experimental study that was followed by a pretest-posttest design with a control group. The statistical population of the study included nurses in Zahedan. Forty nurses were selected using the convenience sampling method and were randomly assigned to the two groups. During the training sessions, the subjects were reduced to 19 ones, and the pretest was conducted on both groups. Then eight 90-minute sessions of training emotion regulation techniques were carried out on the experimental group for two months. The posttest was conducted, one-month after the training. The Connor-Davidson Resilience Scale and the Reef Psychological Well-Being Inventory were used to collect the data. The data analyses were carried out using the Analysis of Covariance. Results: The results indicated that training emotion regulation techniques were effective in increasing resilience and psychological well-being. Moreover, the results showed that .40 of the variances in resilience (P . 0.001) and .20 of the variances in psychological well-being (P . 0.001) were determined in the posttest via the independent variable. Conclusions: Therefore, holding intervention programs based on the emotion regulation techniques are recommended to improve resilience and psychological well-being among nurses.